Accelerating Records Management at CERN. Issue 1 (3rd July 2018) - Short, Andrew
ABSTRACT: In 2015, CERN (European Organization for Nuclear Research) implemented a records management system to manage personnel records dating back to the mid-1950s. This article will look at the situation at CERN before a digital solution was available, what solution was chosen, what customisations were required, and the current situation. There is also some insight into the future direction of the project and remaining goals.